HISTOLOGICAL CHANGES OF WHITE RAT’S STOMACH THAT GIVEN YEAST - Insani, Widia; Suastika, Putu; Budiasa, I Ketut; Berata, I Ketut (Buletin Veteriner Udayana, 2022)
This study aims to determine the histologycal changes of the stomach of white rats given tape yeast. The samples used in this study were 24 female white rats aged 4-5 months, weighing 100-200 grams which were given pelleted feed with the addition of tape yeast. The sample taken was the stomach organ in the corpus region. White rats were grouped into 4 treatments and 6 replications, namely P0: control; P1: giving tape yeast 100 mg/kgBW; P2: 200 mg/kgBW of tape yeast; P3: giving tape yeast 300 mg/kgBW. White rats were dynecropsed on day 22 in all treatment groups. The gastric organs of the corpus region were taken for preparation with Haematoxylin Eosin staining. The variables observed were hemorrhage, inflammation and necrosis. The data obtained were analyzed using the Kruskal-Wallis non-parametric statistical test. If there is a significant difference (P<0.05), the Mann-Whitney test is followed. Based on the results of the Kruskal-Wallis statistical test in all treatment groups there was no significant difference (P>0.05) between the P0 control group and the P1, P2, and P3 treatment groups used. So, it can be concluded that the use of doses of 100 mg/kgBW, 200 mg/kgBW, 300 mg/kg BW has no significant effect on the damage to the gastric organs caused. This could be because the fermentation process of feed mixed with yeast in the stomach is not optimal.